Novel Approaches in Mycotoxins Research: Detection, Prevention and Mode of Action - Ana Juan-García; Daniela Jakšić (Toxins)
Mycotoxins, which are toxic secondary metabolites produced by fungi, pose significant risks to food safety and public health [...]